Effectiveness of Physical Rehabilitation in Symptom Control and Functionality in Patients with Chronic Diseases in Family Medicine - MSc. Maritza Elizabeth Freire Paucar; Gricelda Emperatriz Valencia Olalla; Pedro Renato Flores Brito (International Journal of Medical Toxicology and Legal Medicine, 2024)
Physical rehabilitation plays a critical role in improving the quality of life for patients with chronic diseases, particularly in the field of family medicine, where comprehensive management and continuity of care are essential. This study analyzes the effectiveness of physical rehabilitation in symptom control and functionality in patients with chronic diseases such as diabetes, hypertension, and chronic obstructive pulmonary disease (COPD). Through a quasi-experimental study design with a sample of 150 patients, it was observed that those who participated in physical rehabilitation programs experienced significant improvements in symptom control and function. The results suggest that the implementation of physical rehabilitation programs in family medicine is an effective strategy for the management of chronic diseases.